Multi-purpose fatigue sensor. Part 1. Uniaxial and multiaxial fatigue - M.V. Karuskevich; S.R. Ignatovich; Т.P. Maslak; A. Menou; P.О. Maruschak; S.V. Panin; F. Berto (Fracture and Structural Integrity)
The paper describes the key principles and results of preliminary experiments aimed at the development of new technique for the fatigue life prediction under conditions of biaxial cyclic tension. The foundations of the method were developed early by the numerous tests with monitoring the process of surface deformation relief formation, which is proved to be an indicator of accumulated fatigue damage under uniaxial fatigue. The employed phenomenon was early applied for the development of a family of uniaxial loading fatigue sensors. The formation of strain induced relief has been recently taken into consideration as a part of damage accumulation criteria under biaxial fatigue as well. The home-made testing machine has been designed to implement combined bending and torsion loading that simulates loads experienced by an aircraft wing skin. The experimental evidences on formation and evolution of the deformation relief revealed under conditions of combined loading, supports the proposed concept of biaxial fatigue sensor